Mepolizumab in the management of severe eosinophilic asthma in adults: current evidence and practical experience - Rosalia Emma; Jaymin B. Morjaria; Virginia Fuochi; Riccardo Polosa; Massimo Caruso (Therapeutic Advances in Respiratory Disease, 2018)
Asthma is a chronic inflammatory condition involving the airways with varying pathophysiological mechanisms, clinical symptoms and outcomes, generally controlled by conventional therapies including inhaled corticosteroids and long-acting β 2 agonists. However, these therapies are unable to successfully control symptoms in about 5–10% of severe asthma patients. Atopic asthma, characterized by high immunoglobulin (Ig)E or eosinophilia, represents about 50% of asthmatic patients. Interleukin (IL)-5 is the main cytokine responsible of activation of eosinophils, hence therapeutic strategies have been investigated and developed for clinical use. Biologics targeting IL-5 and its receptor (first mepolizumab and subsequently, reslizumab and benralizumab), have been recently approved and used as add-on therapy for severe eosinophilic asthma resulting in a reduction in the circulating eosinophil count, improvement in lung function and exacerbation reduction in asthma patients. Despite these biologics having been approved for stratified severe asthma patients that remain uncontrolled with high doses of conventional therapy, a number of patients may be eligible for more than one biologic. Presently, the lack of head-to-head studies comparing the biological agents among themselves and with conventional therapy make the choice of optimal therapy for each patient a challenge for clinicians. Moreover, discontinuation of these treatments, implications for efficacy or adverse events, in particular in long-term treatment, and needs for useful biomarkers are still matters of debate. In this review we evaluate to date, the evidence on mepolizumab that seems to demonstrate it is a well-tolerated and efficacious regimen for use in severe eosinophilic asthma, though more studies are still required.